Attitude and competence to use Madrasati (M LMS) among school teachers in Riyadh, Saudi Arabia - Alharbi, Hamad Muaybid; Ab Jalil, Habibah; Omar, Muhd Khaizer; Mohd Puad, Mohd Hazwan (Little Lion Scientific, 2022)
Attitude and competence are two factors that affect the acceptance and utilization of new technology in education. In this regard, the full utilization of the new Madrasati (M) technology among teachers in public schools in Riyadh is still challenging. Thus, this study aimed to determine the moderating effect of gender and age on the relationship between teachers' attitudes and competence in utilizing M LMS technology in public schools in Riyadh, as mediated by behavioral intention. The survey method and quantitative approach were employed. Data were collected from 374 teachers out of the population of 13,782 teachers in schools implementing M LMS in Riyadh. The finding of the tested model showed a potential positive mediation role of BI on attitude (ATT) and competence (COM) to use M LMS among public school teachers in Riyadh. The overall mean showed that ATT1 was high among the eight items used after CFA testing, while ATT11 had the lowest mean score. Among the seven items used for CFA testing, COM18 had the highest mean score. The results also indicated that the utilization of M LMS is high among teachers. They visit M LMS three times a week and spend between 61-90 minutes per visit. The finding also revealed the direct effect of COM over ATT on M LMS utilization through mediator BI. The relationship between ATT and M LMS, as moderated by gender and age, is statistically insignificant, suggesting that ATT has no significant moderating effect on M LMS utilization among teachers. Meanwhile, COM to use M LMS positively and significantly affects M LMS acceptance and utilization in Riyadh. In conclusion, the COM to use M LMS plays a more crucial role in accepting and utilizing public school teachers in Riyadh than their ATT. Therefore, it is recommended that future studies use a longitudinal design to obtain more accurate findings.